(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The main objective of the current study is to enhance the solubility and dissolution of poorly water-soluble drug flurbiprofen, a propionic acid derivative, used as non-steroidal anti-inflammatory drug by formulating into solid dispersion (SD) employing various hydrophilic polymers as carriers in the formulation. Materials and Methods: The solubility of drug in various polymers such as AQOAT AS, PVP-K30, hydroxypropryl methyl cellulose, Soluplus, and Kollidon VA 64 was studied. Total 15 SD formulations were prepared by solvent evaporation technique with different polymers and were evaluated for particle size analysis, % practical yield, drug content determination, and in vitro dissolution studies. Results: Based on the evaluation parameters and dissolution studies, SD6 was found to be optimized formulation. The SD6 prepared using flurbiprofen:AQOAT AS:sodium lauryl sulfate as drug:polymer:surfactant in 1:5:2 ratios showed maximum drug release of 99.86 in 15 min when compared with other formulation and the solubility of the formulation SD6 was enhanced 44 folds when compared to that of pure drug. Drug excipient compatibility studies were conducted using FTIR and XRD and scanning electron microscope (SEM) studies were also conducted. FTIR studies showed the compatibility between drug and polymers. XRD and SEM studies showed that the optimized formulation was in amorphous form which fetched in better dissolution of the drug from the SD formulation when compared to the pure drug. Conclusion: This indicates the formulation technology employed with a potential of enhancing bioavailability of poorly water-soluble drug by improving its dissolution rate.